2018
DOI: 10.5897/ijbc2018.1211
|View full text |Cite
|
Sign up to set email alerts
|

Conservation status assessment of native vascular flora of Kalam Valley, Swat District, Northern Pakistan

Abstract: In the present study, conservation status of important vascular flora found in Kalam valley was assessed. Kalam Valley represents the extreme northern part of Swat District in KPK Province of Pakistan. The valley contains some of the precious medicinal plants. 245 plant species which were assessed for conservation studies revealed that 10.20% (25 species) were found to be endangered, 28.16% (69 species) appeared to be vulnerable. Similarly, 50.6% (124 species) were rare, 8.16% (20 species) were infrequent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…They stressed that the basic reason is over grazing, uses as a source of medicine, timber wood, fuel wood and other anthropogenic activities. Bano et al (2013); Khan et al (2014); Ullah and Rashid (2014); Bakht et al (2018) documented the conservation status of Azad Jammu and Kashmir, Himalayan, Region Poonch valley, Azad Kashmir, Mankial valley Hindukush Range, and Kalam valley. It was observed that majority of plants became extinct because of their high medicinal potential, over grazing, unwanted deforestation and other anthropogenic activities.…”
Section: Conservation Status Of the Floramentioning
confidence: 99%
See 1 more Smart Citation
“…They stressed that the basic reason is over grazing, uses as a source of medicine, timber wood, fuel wood and other anthropogenic activities. Bano et al (2013); Khan et al (2014); Ullah and Rashid (2014); Bakht et al (2018) documented the conservation status of Azad Jammu and Kashmir, Himalayan, Region Poonch valley, Azad Kashmir, Mankial valley Hindukush Range, and Kalam valley. It was observed that majority of plants became extinct because of their high medicinal potential, over grazing, unwanted deforestation and other anthropogenic activities.…”
Section: Conservation Status Of the Floramentioning
confidence: 99%
“…The loss of biodiversity characterizes one of the most persistent environmental challenges (Ali et al 2018). In the preceding eight years, 49 countries round the world have devoted to reinstating 150 million ha of ruined and deforested land by 2020 and 350 million ha by 2030 to protect the valuable biodiversity (Bakht et al 2018).…”
Section: Introductionmentioning
confidence: 99%